2019
DOI: 10.1093/oso/9780190056483.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Outrageous Idea of Christian Teaching

Abstract: There are thousands of Christian professors, many of whom claim “Christian” as their primary identity and teaching as their primary responsibility. Much of the current literature about the integration of faith and learning focuses on the differences between Christian scholarship and Christian teaching. As a result, few books explore how Christian identity, or a particular Christian identity (e.g., Baptist, Anglican), shapes teaching. In addition, few works examine what identity-influenced teaching outside of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…K-12 teachers in this study reported more influence of faith on what students learn (course content) than on how they learn (instructional strategies). A similar content bias has been reported in Christian higher education (Glanzer and Alleman, 2019;Smith, 2018;Smith et al, 2014Smith et al, , 2021.…”
Section: Course Content and Instructional Strategiessupporting
confidence: 73%
See 2 more Smart Citations
“…K-12 teachers in this study reported more influence of faith on what students learn (course content) than on how they learn (instructional strategies). A similar content bias has been reported in Christian higher education (Glanzer and Alleman, 2019;Smith, 2018;Smith et al, 2014Smith et al, , 2021.…”
Section: Course Content and Instructional Strategiessupporting
confidence: 73%
“…In light of the literature from higher education, especially the CCCU study by Glanzer and Alleman (2019), it is surprising that K-12 teachers' responses did not differ in any statistically significant way when grouped by theological tradition. I will suggest three possible explanations.…”
Section: Theological Traditionmentioning
confidence: 94%
See 1 more Smart Citation
“…As we turn to the question of what kinds of practices might count as embodiments of faith and sites where schools and students interact, we intersect with a significant body of work on the nature of social practices, Christian practices, and their intersection with educational practices (e.g. Cooling and Green, 2015; Dykstra, 2005; Glanzer and Alleman, 2019; Griffiths, 1999; Lave and Wenger, 1991; MacIntyre, 1984; Peachey, 2020; DI Smith and Smith, 2011; DI Smith et al., 2020; Wenger, 1999; Volf, 2002). As framed in this literature, practices are not the less intellectual half of a theory-practice or a belief-practice divide.…”
Section: Christian Practicesmentioning
confidence: 99%
“…In short, we worry that administrators responsible for student success at Christian colleges and universities (some of whom were included in the study of Christian student affairs professionals) have yet to allow their faith to fully animate their approach to student success (Davis, 2017;Glanzer et al, 2020;Glanzer and Alleman, 2019). When something is animated, it is brought to life (think of the vision of the valley of dry bones in Ezekiel 37, Christ's resurrection, or our own necessary experience of being "born again").…”
Section: A Theological Interpretation Of the Current Landscapementioning
confidence: 99%